(untitled) (Journal of the College of Basic Education, 2022)
Samples of X%Al2O3 ( X = 17.85, 28.05, 87.98 and 95.63 ) were prepared from Iraqi kaolin, after calcinations process, by the method of evaporation. From the temperature dependence of capacitance, the temperature dependence of dielectric constant are studied for the samplesof annealed powders of various Al2O3 contents in the frequency range 1KHz – 1MHz.